The eschatological banquet: hidden transcripts in the funerary banquet scenes of the Christian catacombs - Smith, E (2010)
Like most images found in the Christian catacombs of Rome, the banquet scenes came into Christian use after long employment in other Greco-Roman contexts. The funerary banquet frescoes are iconographically similar to the “symposium” motif found in non-Christian contexts, and their Christian meaning would seem at first to be in continuity with others of the type. This continuity has led many to understand the image’s function just this way, as continuous with similar non-Christian uses in antiquity, and to conclude that there was nothing particularly Christian about Christians’ use of the motif – it was just rote reproduction, or at best adapted reproduction. This paper, however, will argue that the Christian use of the banquet scenery in the Roman catacombs was intentional and starkly different from other ancient uses, both in its implementation and its eschatological undertones. It will understand the banquet scenes as an example of what James C. Scott calls a “hidden transcript of the subordinate,” in which a subordinate group (Christians, in this case) produce “transcripts,” or discourse, about a dominant group (the Roman Empire, in this case) in such a way that the transcripts are unintelligible to anyone outside of the subordinate group. This paper will read the early Christian banquet images as such transcripts, employed as instruments of resistance to imperial persecution. It will view the banquet scenes as a Christian re-appropriation of culturally current imagery to express Christian solidarity and purpose in the face of persecution, and to affirm eschatological hope in the midst of trouble.